Ein Gespräch über das Iwalewahaus: János Riesz im Interview mit Ulli Beier (2002) (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2002)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Transcription; Interviews